Methods to coalesce fluorinated Pickering emulsions. Issue 31 (27th July 2017) - Pan, Ming; Lyu, Fengjiao; Tang, Sindy K. Y.
Abstract : Comparison of different methods to merge fluorinated Pickering emulsions provides a practical guide for applications in droplet microfluidics. Abstract : This work surveys methods to coalesce water-in-fluorocarbon emulsions stabilized by amphiphilic nanoparticles (NPs) for applications in droplet microfluidics. Most droplet assays to date have relied on one type of surfactant consisting of perfluorinated polyether and polyethylene glycol (PFPE–PEG) to stabilize the drops against coalescence. Nonetheless, this surfactant is known to have several limitations, the most severe of which being its mediation of inter-drop molecular transport leading to the cross-talk of droplet contents. Previously we addressed this challenge by replacing surfactants with amphiphilic NPs. The merging of NP-stabilized drops, however, is known to be more difficult than that of surfactant-stabilized drops due to the high energy barrier to desorb NPs from the interface. Here we compare the efficiency of droplet merging by different methods including centrifugation, freeze–thaw cycling, addition of chemical additives, and the application of an electric field. The results of this work are useful as a selection guide for the appropriate method to merge NP-stabilized drops.